A critical analysis of the harmony search algorithm—How not to solve sudoku. (December 2015) - Weyland, Dennis
Abstract: This article presents a critical analysis of the harmony search metaheuristic framework. We formally prove that the harmony search algorithm is a special case of evolution strategies. First, this implies that the harmony search algorithm itself does not offer any novelty, apart from using a different terminology. Second, the performance of the best harmony search algorithm is always bounded by the performance that can be obtained by evolution strategies. Additionally, more than a decade of research about harmony search has not revealed any other sort of novelty or has led to any new insights or significant contributions in the field of heuristics. In short, there is no reason for harmony search to exist as a separate metaheuristic framework. Based on these findings, we carefully examine the results found in the paper Harmony search algorithm for solving sudoku . A theoretical investigation and a reimplementation of the harmony search algorithm both reveal that these results are fundamentally flawed.